Teaching Reading Comprehension through Survey, Question, Read, Recite, Review (SQ3R) Strategy - Sakinah Sakinah; Asnawi Muslem; Diana Fauzia Sari (Research in English and Education Journal, 2017)
This study was a quantitative research about the implementation of Survey, Question, Read, Recite, Review (SQ3R) a strategy for solving specific questions individually and for helping students to memorize teaching materials, in teaching reading descriptive text. It was intended to find out whether or not SQ3R strategy could improve students’ reading comprehension. The subject of this study was all students of class VIII-5 of SMP Negeri 8 Banda Aceh which was chosen by using simple random sampling. The reason for conducting this study was due to the fact that students’ reading comprehension was still low. Moreover, the design used in this study was one group pre-test post-test design. In this study, the data was collected through pre-test, treatment and post-test. From the result of the study, it is found that mean of post-test (60) was higher than mean of pre-test (30.95). It indicated that the students’ post-test scores were increased from their pre-test scores Moreover, based on t-test formula, the result of t-score (7.83) was higher than t-table (2.086). It means that the alternative hypothesis (Ha) was accepted, while the null hypothesis (H0) was rejected. Hence, it can be concluded that SQ3R strategy can improve the students’ reading comprehension in descriptive text.